Molecular characterization of fowl adenovirus isolated from commercial broiler farms in Malaysia - S. N., Syazana; Tan, S. W.; Omar, Abdul Rahman (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2018)
A total of 55 PCR-positive cases of fowl adenovirus (FAdV) were detected from commercial broiler farms in Malaysia between 2016 and 2017. However, sequence analysis of the FAdV is largely unknown. In this study, molecular characterization of three Malaysian pathogenic FAdV isolates namely UPM/FAdV/392/2017, UPM/FAdV/420/2017 and UPM/FAdV/424/2017 was characterized. Virus isolation was carried out by inoculating 10-day-old SPF embryonated eggs with liver homogenate via chorioallantoic membrane (CAM) route. Virus inoculation result showed 100% mortality of embryo within 7 days of incubation with typical lesion associated with FAdV such as thickening of CAM and multifocal liver necrosis. Pooled CAM and liver of the inoculated chicken embryo were processed for viral DNA extraction and followed with PCR to amplify 1219 bp hexon gene of FAdV. Nucleotide sequence analysis of the amplicon revealed high similarity reaching >99% identity where all of the isolates belonged to a single serotype of FAdV-8b, species E. Pairwise distance analysis between the current isolates with previous Malaysian isolates isolated between 2004 and 2008 also revealed high similarities at the nucleotide level (>95% identity). In addition, the result of phylogenetic analysis also consistent with the clustering of Malaysian FAdV isolates into groups FAdV-8b species E.